(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
From 1988 till 1993 laboratory and field trials were carried out on the damage caused by the larvae of two species of Dipteran Chironomids, Cricotopus sylvestris (F.) and Chironomus pallidivittatus (Mall.), very frequently found in the rice fields of the Verona province. The former appeared to cause the most damage since it attacks both the shooting seeds and the leaves of young plants. This paper deals with the damage caused by both species. The larvae of 3rd and 4th instar appear to be the most injurious. Rice plants are most vulnerable in the stage included from seedling to rooting. The most frequent damage is represented by the destruction of the root apparatus. In the laboratory trials a population density of 10 larvae/dm2 may cause an 80% loss of plants. Although the loss of seeds is important, in the field trials the damage was seen to be much lower in comparison to the laboratory trials.